Contracting, Contesting, and Co-Optation: Civil Society Organizations' Strategies under New Institutional Arrangements in Brazil. Issue 1 (April 2015) - Wampler, Brian; Touchton, Michael
Civil society has exploded in Latin America as democratization has continued over the last 30 years. Civil society organizations (CSOs) are thought to improve governance and oversight and to increase social capital. Nonetheless, we have limited knowledge about what motivates CSOs' political strategies, which include participating in formal political institutions, attending demonstrations, and providing services. We build knowledge here by evaluating data from a unique survey of nine hundred CSOs across seven Brazilian cities. Our findings showcase several parallel processes: poorer CSOs continue to rely on the state and actively participate in political processes despite protesting at greater rates than wealthier CSOs; therefore, we contend that institutional and political process arguments better explain poorer CSOs' behavior. We also argue that relatively wealthy CSOs' disengagement reflects greater resource mobilization, more professionalization, and an increase in social capital. Our results show that multilayered explanations improve our understanding of CSO behavior and state-society relations in Brazil and Latin America.